The impact of economic uncertainty, precarious employment, and risk attitudes on the transition to parenthood - Christian Schmitt (Advances in Life Course Research, 2021)
This study investigates how precarious employment throughout the life course affects the fertility behavior of men and women in Germany, and how risk attitudes moderate exposure to objectively given uncertainty. Analyzing data from the German Socio-Economic Panel (SOEP) study from 1990 to 2015, I find that men and women have become quite similar in their fertility behavior: Stable employment accelerates family formation, whereas discontinuous and precarious employment delays it. With regard to risk attitudes, risk-averse women show the highest likelihood of family formation. They appear to choose a family- and parenthood-centered path in their life course that provides them with stability and social approval when unstable career prospects and uncertain employment are unable to provide these resources.
Keywords: 300; Economic uncertainty; Precarious employment; Welfare State; Germany; Parenthood decision; Life-course; Event-history analysis